CAR T-cell therapy for a relapsed/refractory acute B-cell lymphoblastic lymphoma patient in the context of Li-Fraumeni syndrome. Issue 1 (28th April 2020) - Chen, Liting; Xu, Bin; Long, Xiaolu; Gu, Jia; Lou, Yaoyao; Wang, Di; Cao, Yang; Wang, Na; Li, Chunrui; Wang, Gaoxiang; Wang, Ying; Zhu, Li; et al.
Abstract : Background: Li-Fraumeni syndrome (LFS) is characterized as an autosomal dominant cancer predisposition disorder caused by germline TP53 gene mutations. Both primary and therapy-related hematopoietic malignancies with LFS are associated with dismal outcomes with standard therapies and even allogenic stem cell transplantation (SCT). Case presentation: We reported a relapsed/refractory acute B-cell lymphoblastic lymphoma (B-LBL) patient in the context of LFS. He was identified to harbor a TP53 c.818G>A (p.R273H) germline mutation, and his family history was significant for rectal carcinoma in his father, an unknown cancer in his sister and acute lymphoblastic leukemia in his brother and one of his sons. The patient received murine monoclonal anti-CD19 and anti-CD22 chimeric antigen receptor (CAR) T-cell "cocktail" therapy and achieved complete remission with negative minimal residual disease (MRD), as assessed by morphology and multiparameter flow cytometry. Fifteen months after murine monoclonal CAR T-cell "cocktail" therapy, the patient's B-LBL recurred. Fortunately, a round of fully human monoclonal anti-CD22 CAR T-cell therapy was still effective in this patient, and he achieved CR again and continued to be followed. Each time after infusion, the CAR T-cells underwent extremely rapid exponential expansion, which may be due to the disruption of TP53, a gene that can functionally control cell cycle arrest. Grade 4 and grade 1 cytokine release syndrome occurred after the first and second rounds of CAR T-cell therapy, respectively. Conclusions: This case provides the first report of the use of CAR T-cell therapy in a hematologic malignancy patient with LFS. As traditional chemotherapy and allogenic SCT are not effective therapy strategies for patients with hematologic malignancies and LFS, CAR T-cell therapy may be an alternate choice. ChiCTR-OPN-16008526 and ChiCTR1900023922.